KOMUNIKASI LINTAS BUDAYA ANTARA PENGLINGSIR PURI KANGINAN BULELENG DENGAN UMAT MUSLIM DALAM PRAKTIK MENYAMA BRAYA DI KELURAHAN KAMPUNG SINGARAJA KABUPATEN BULELENG PROVINSI BALI - Kusuma Negara, Eka Prasetya; Yuliani, Ni Made; Suwantana, I Gede (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This study examines cross-cultural communication between Penglingsir Puri Kanginan Buleleng and Muslims community in Kampung Singaraja Subdistrict, Bali. The Muslims community in this area are descendants of the Blambangan Islamic Warriors, followers of the King of Buleleng, I Gusti Anglurah Panji Sakti. The Islamic Warriors were granted land by the King of Buleleng in 1711. Despite their different religious and cultural backgrounds, communication between the two groups has been intense, resulting in the practice of